(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Innovation is important to every human being on the planet. Due to the limitations of the various resources available in the world, which are steadily dwindling and are about to run out. Consequently, businesses, especially those that rely on natural resources, must try to find ways to make their businesses survive in a sustainable way, which is clearly a serious problem in the world’s economy. Objective of this research is to study the causal influence of innovations affecting added value creation of social enterprises.Theory in this paper is Diffusion of Innovation theory.Research Methodology in the term of sample for structural equation conceptual analysis should be at least 200 sample sizesfrom social entrepreneurs in Thailand. Researcher analysis statistics with the structural equation model. The result found thatResults of the framework analysis of the modified structural equation model. The added value (t=4.15) was statistically significant. and there was a statistically positive correlation with the intrinsic variables in competitiveness (t = 4.57), which was a new finding in the research. The intrinsic variables in value-added were statistically significant (t=3.60), 3. The external latent variables in process innovation were related to the intrinsic variables in the valueadded aspect (t=2.89), and 4. Finally, there was a statistically significant relationship between the external latent variables in product innovation and the internal latent variables in marketing innovation. (t=6.41) The results of the analysis of the causal influence between the internal latent variable and the internal latent variable found that 1. The latent variable in the value-added aspect had a statistically significant relationship with the latent variable in the competitive advantage. (t =20.16) Recommendation:develop products at the corporate level or entrepreneurs to be able to create added value, such as creating new modern packaging formats, developing sales promotions through social media. Create a new marketing strategy create a marketing experience with consumers. Moreover, At the national level, there are departments as well as to promote products to be able to compete with international is constantly evolving Encourage quality products to meet national standards including packaging that must meet the needs of consumers in each region.